Advances in Patient-Specific Induced Pluripotent Stem Cells Shed Light on Drug Discovery for Amyotrophic Lateral Sclerosis. Issue 9 (September 2018) - Lee, Jui-Hao; Liu, Jen-Wei; Lin, Shinn-Zong; Harn, Horng-Jyh; Chiou, Tzyy-Wen
Induced pluripotent stem cells (iPSCs), which are generated through reprogramming adult somatic cells by expressing specific transcription factors, can differentiate into derivatives of the three embryonic germ layers and accelerate rapid advances in stem cell research. Neurological diseases such as amyotrophic lateral sclerosis (ALS) have benefited enormously from iPSC technology. This approach can be particularly important for creating iPSCs from patients with familial or sporadic forms of ALS. Motor neurons differentiated from the ALS-patient-derived iPSC can help to determine the relationship between cellular phenotype and genotype. Patient-derived iPSCs facilitate the development of new drugs and/or drug screening for ALS treatment and allow the exploration of the possible mechanism of ALS disease. In this article, we reviewed ALS-patient-specific iPSCs with various genetic mutations, progress in drug development for ALS disease, functional assays showing the differentiation of iPSCs into mature motor neurons, and promising biomarkers in ALS patients for the evaluation of drug candidates.